Export product quality between China and Asian countries - Eshraghi, Mastooreh; Ismail, Normaz Wana (Springer, 2013)
This study aims to measure the export product quality improvement for trade between China and five selected Asian countries namely, India, Malaysia, Thailand, the Philippines and Indonesia using product quality value method of Azhar and Elliott (Rev World Econ 139(3):419–439, 2006). Vertical intra-industry trade high is considered as high quality products. We examined disaggregated four-digit standard international trade classification data, for the period of 2000 to 2008. The results propose that Malaysia has the highest benefits of intra-Industry trade with China while, Philippines and India are in second and third places. Export product quality improvement of Thailand is clearly evident in the second period, where with 87.88 % growth of high quality product can be a prospective partner choice in trading for China. It is worth for China to focus on Thailand as a significant importer on high quality products.